2017
DOI: 10.1590/1809-4422asoc66r2v2032017
|View full text |Cite
|
Sign up to set email alerts
|

The Interdependence of Climate and Socioeconomic Vulnerability in the Abc Paulista Region

Abstract: This study aimed to analyze the socio-economic, demographic, health and climatic vulnerabilities in the ABC Paulista region that comprises the municipalities of Santo André, São Caetano do Sul, São Bernardo do Campo, Mauá, Diadema, Rio Grande da Serra and Ribeirão Pires. The vulnerabilities were analyzed through the construction of indices based on the aggregation of indicators collected in the IBGE census and climate indices of extreme rainfall. The municipalities of Diadema and Mauá were identified as the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
(7 reference statements)
0
7
0
1
Order By: Relevance
“…However, despite the particularities of air pollution sources and dynamics, few atmospheric studies were dedicated to the ABC region. Most of them focused on air pollution health impacts (e.g., Chiarelli et al, 2011;Negrete et al, 2010;Silva et al, 2017), on urban climate (Valverde, 2017;Valverde et al, 2020), and a few on ambient air pollution measurements (Saiki et al, 2007;Savóia et al, 2009;Caumo et al, 2017;Guimarães et al, 2019). This study contributes to the filling of this gap, describing the variability of air pollutant concentrations in the ABC region, accounting for its particularities on pollution sources and atmospheric conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the particularities of air pollution sources and dynamics, few atmospheric studies were dedicated to the ABC region. Most of them focused on air pollution health impacts (e.g., Chiarelli et al, 2011;Negrete et al, 2010;Silva et al, 2017), on urban climate (Valverde, 2017;Valverde et al, 2020), and a few on ambient air pollution measurements (Saiki et al, 2007;Savóia et al, 2009;Caumo et al, 2017;Guimarães et al, 2019). This study contributes to the filling of this gap, describing the variability of air pollutant concentrations in the ABC region, accounting for its particularities on pollution sources and atmospheric conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The outliers identified in the boxplot diagram in all cities occurred in 2010. That year, there was a high frequency of flooding and landslide events in the municipalities of ABC Paulista (Fernandes and Valverde, 2017;Valverde, 2017;Damasceno et al, 2021). The most significant outlier occurred in 2010 (Figure 3).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have analyzed rainfall in the municipalities of ABC Paulista, considering longer time series (Fernandes and Valverde, 2017;Valverde, 2017;Valverde et al, 2018) and grouping data series from nearby rain gauges for analysis of trends and variabilities. Valverde et al (2018), analyzing two series of data from 1968-1998 to 1999-2014, identified an increase in rainfall in January in Diadema, São Caetano do Sul, São Bernardo do Campo, and Santo André, accompanied by a reduction of annual rainfall from one period to another.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, o estado de vulnerabilidade ambiental de um território deveria ser melhor considerado nos processos de planejamento e gestão (Jordão e Moretto, 2015). Muitas dessas investigações têm utilizado a abordagem sistêmica para compreender as vulnerabilidades de diferentes sistemas a distintos riscos como, por exemplo, risco climático (Valverde, 2017); risco à erosão (Fushimi, 2013;Sokoloski et al, 2019) e risco à inundações (Prates e Amorim, 2017), etc.…”
Section: Introductionunclassified